Optimum period of structural health monitoring for ageing fixed offshore platform - Zulkifli, Muhammad Aniq Razin (2022)
The industry of oil and gas began in Malaysia in the early 1900s and has evolved over 115 years. Since 1990, Malaysia’s gasoline consumption has increased at an annual rate of 7.2%, reaching 44.9 Mtoe in 2008. The expected demands of oil and gas are increasing from 2010 up until 2026. The oil and gas operators are pressured to improve their recovery of oil and gas resources hence needs to extend the operation of the platform beyond its design life. In order to do that, reliability engineering has become a common practice in the Malaysian oil and gas industry to access the integrity and requalification of offshore platform in the late 1990s. The common design life of the fixed offshore structure ranges between 20-30 years. In 2019, PETRONAS operates over 200 fixed offshore structures in Malaysian waters, which over half of them have outlived their design lives. Various standards and guidelines are introduced globally to ensure the extended lifetime of the fixed offshore platforms are safe to be used. However, the current development of structural health monitoring is focusing on the development of the technology and only limited guidelines and standards are discussing on the optimum or recommended duration for the monitoring. In this study, structural health monitoring (SHM) and Wave Radar system are used to collect data for acceleration of the platform and the height of wave hitting the platform which utilizes vibration based-damage detection. The data is then converted using Fast Fourier Transform to convert the time domain signal into a frequency domain signal. The output of the conversion is used to measure the impacts of different SHM duration assessments on the accuracy of the results hence determining the most optimum duration for the SHM assessment period. Six (6) test platforms were selected with four (4) different types of platform were analysed which are one-legged, three-legged, four-legged, and six-legged to fulfil perspective 1 that focused on impacts of monitoring period on different platforms’ specifications. Meanwhile, another two (2) four-legged platform were analysed to fulfil perspective 2 which focus on the data reliability of the study. The platform’s more robust structure reduces its susceptibility to environmental changes. One-legged platforms require a 16-day SHM campaign to assess structural health with 99.71% accuracy. SHM campaigns for three-legged platforms take 14 days to reach 99.53%. This study proposes that four-legged platforms should be monitored for 10 days to achieve 99.52% accuracy. The six-legged SHM platform reaches 99.59% accuracy in two days. This study confirmed that the optimum monitoring period for static platform (i.e., 4-legged and 6-legged) is shorter compared to dynamics platform (i.e., 1-legged and 3-legged platforms) to fulfil higher level of accuracy. Engineers can use the optimum monitoring period proposed as a benchmark to define the limit for monitoring periods, optimising SHM costs for offshore structures and improving accuracy. Future SHM deployment costs could be reduced by improved accuracy and measurement period.